THEORETICAL AND METHODOLOGICAL ASPECTS OF OUT-TECHNOLOGIES IMPLEMENTATION IN THE PRACTICE OF PUBLIC ADMINISTRATION - Ganushchyn S.N. (Pressing Problems of Public Administration, 2015)
The modern out-technologies in administration system were researched. Theoretical and methodological analysis of outsourcing, outstaffing, insourcing, outtasking and outplacement was performed. Тhe possibility of their use in public administration were proven out, espesially to implement the priorities of Sustainable Development Strategy «Ukraine-2020».